Effects of Condom Use on Human Immunodeficiency Virus Transmission Among Adolescent Sexual Minority Males in the United States: A Mixed Epidemiology and Epidemic Modeling Study. Issue 12 (7th December 2021) - Katz, David A.; Hamilton, Deven T.; Rosenthal, Elizabeth M.; Wang, Li Yan; Dunville, Richard L.; Aslam, Maria; Barrios, Lisa C.; Zlotorzynska, Maria; Sanchez, Travis H.; Sullivan, Patrick S.; Rosenberg, Eli S.; Goodreau, Steven M.
Abstract : An epidemiologic and modeling study found that condom use remained relatively low and stable among US adolescent sexual minority males from 2011 to 2017 and moderate increases may reduce human immunodeficiency virus transmission. Supplemental digital content is available in the text. Abstract : Background: We examined condom use patterns and potential population-level effects of a hypothetical condom intervention on human immunodeficiency virus (HIV) transmission among adolescent sexual minority males (ASMM). Methods: Using 3 data sets: national Youth Risk Behavior Survey 2015 to 2017 (YRBS-National), local YRBS data from 8 jurisdictions with sex of partner questions from 2011 to 2017 (YRBS-Trends), and American Men's Internet Survey (AMIS) 2014 to 2017, we assessed associations of condom use with year, age, and race/ethnicity among sexually active ASMM. Using a stochastic agent-based network epidemic model, structured and parameterized based on the above analyses, we calculated the percent of HIV infections averted over 10 years among ASMM ages 13 to 18 years by an intervention that increased condom use by 37% for 5 years and was delivered to 62% of ASMM at age 14 years. Results: In YRBS, 51.8% (95% confidence interval [CI], 41.3–62.3%) and 37.9% (95% CI, 32.7–42.3%) reported condom use at last sexual intercourse in national and trend data sets, respectively. In AMIS, 47.3% (95% CI, 44.6–49.9%) reported condom use at last anal sex with a male partner. Temporal trends were not observed in any data set ( P > 0.1). Condom use varied significantly by age in YRBS-National ( P < 0.0001) and YRBS-Trends ( P = 0.032) with 13- to 15-year-olds reporting the lowest use in both; age differences were not significant in AMIS ( P = 0.919). Our hypothetical intervention averted a mean of 9.0% (95% simulation interval, −5.4% to 21.2%) of infections among ASMM. Conclusions: Condom use among ASMM is low and appears to have remained stable during 2011 to 2017. Modeling suggests that condom use increases, consistent with previous interventions, have potential to avert 1 in 11 new HIV infections among ASMM.